2020
DOI: 10.1111/jfbc.13474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preharvest application of calcium chloride, putrescine, and salicylic acid on antioxidant system and biochemical changes of two Indian jujube genotypes

Abstract: The effects of the preharvest application of calcium chloride (1 and 2%), salicylic acid (1 and 2 mM), and putrescine (1 and 2 mM) on the quality attributes and biochemical changes of two ber (Ziziphus mauritiana Lamk.) genotypes ("Sibi" and "Khormaee") were investigated at harvest and after 30 days of storage (5 ± 1°C and 85 ± 5% RH). The results showed that softening and weight loss in the treated fruit were significantly lower in comparison with the control. The antioxidant capacity of the fruit was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…These radicals have the potential to exert detrimental effects on cellular tissues [41]; hence, the variations in MDA content among different growing seasons could be directly associated with the abiotic conditions in each growing season. The observed reduction in MDA content in putrescine-treated trees may be associated with better control of the antioxidant balance in the evaluated tissues, as reported previously [25][26][27][28][29][30][31][32][33][34]. Although there was no dose-dependent effect in the 'Prime Giant' cultivar (Figure 1A), this effect was indeed observed in the 'Sweetheart' cultivar (Figure 1B).…”
Section: Effect Of Exogenous Putrescine On Sweet Cherry Frost Toleran...supporting
confidence: 83%
See 1 more Smart Citation
“…These radicals have the potential to exert detrimental effects on cellular tissues [41]; hence, the variations in MDA content among different growing seasons could be directly associated with the abiotic conditions in each growing season. The observed reduction in MDA content in putrescine-treated trees may be associated with better control of the antioxidant balance in the evaluated tissues, as reported previously [25][26][27][28][29][30][31][32][33][34]. Although there was no dose-dependent effect in the 'Prime Giant' cultivar (Figure 1A), this effect was indeed observed in the 'Sweetheart' cultivar (Figure 1B).…”
Section: Effect Of Exogenous Putrescine On Sweet Cherry Frost Toleran...supporting
confidence: 83%
“…Additionally, as with many other elicitors, putrescine has been demonstrated to be involved in the stimulation of energy supply pathways, which is critical in energy-demanding periods, such as abiotic stress and senescence [28]. Positive effects on fruit quality have been demonstrated through the application of preharvest treatments based on putrescine in mango [29], plum [30,31], jujube [32], and pears [33] with additional cold storage tolerance benefits in this fruit [34]. This effect has been associated with an increase in bioactive compounds and antioxidant levels.…”
Section: Introductionmentioning
confidence: 99%
“…Shanbehpour et al. (2020) studied the effect of CaCl 2 on quality attributes and biochemical changes of ber fruit. They reported that fruit softening and PPO activity were reduced, whereas POD and catalase activity were increased after the CaCl 2 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Torres et al (2010), where the effect of postharvest warm dipping of atemoya fruit in 6% CaCl 2 at 20-40 • C for 20 min showed a decrease in PPO and POD activity till the sixth day of fruit storage at room temperature. Shanbehpour et al (2020) studied the effect of CaCl 2 on quality attributes and biochemical changes of ber fruit. They reported that fruit softening and PPO activity were reduced, whereas POD and catalase activity were increased after the CaCl 2 treatment.…”
Section: Effect Of Cacl 2 Treatmentmentioning
confidence: 99%
“…It has been discovered that calcium chloride prevents weight loss in strawberries (Nguyen et al, 2020), apple cv. Red Delicious (Ranjbar et al, 2018), and Indian jujube fruits (Shanbehpour et al, 2020). This might be attributable to a decrease in respiration rate and changes in water permeability‐related cell wall characteristics.…”
Section: Resultsmentioning
confidence: 99%